Flaubert : la tour d’ivoire pour y mieux voir - Luca Pietromarchi (Revue Italienne d'Etudes Françaises)
This article proposes to recognize in the figure of the ivory tower, as it appears in Flaubert’s letters, a questioning of the function that Romanticism assigns to it, namely to signify a choice of isolation with regard to the political present and to historical actuality. This model is, it is true, the object of a continuous evocation, but it never reaches an effective actualization. Another will be its function: the overhanging point of view and the distance that the tower imposes on reality will not serve to erase it, but it will rather allow its wider contemplation.